Opportunistic pathogens are associated with deteriorated clinical parameters in peri-implant disease (2020)
Objectives: To assess the association between Gram-negative enteric rods and Pseudomonas with the clinical parameters in peri-implant disease. Materials and Methods: Patients treated with implants and diagnosed with peri-implant mucositis and/or peri-implantitis participate in this cross-sectional research. Unusual microorganisms from the implants were recognized using MALDI-TOF mass spectrometry. Linear regression models were applied. Results: A total of 103 implants were evaluated in thirty-one participants. Gram-negative enteric rods/Pseudomonas were observed in 47 implants (46%). Interestingly, there were differences in probing pocket depth (PPD), clinical attachment loss (CA), and bleeding on probing (BOP) between the groups, where implants with the presence of Gram-negative enteric rods/Pseudomonas presented deteriorated clinical parameters (p <.0001). The crude and adjusted linear regression models for PPD in peri-implant mucositis, PPD in peri-implantitis, CA in peri-implantitis, and BOP in peri-implant disease present significant ßs, demonstrating deteriorated parameters (p <.0001) in the presence of Gram-negative enteric rods/Pseudomonas. Besides, the model for CA in peri-implantitis showed that cemented restored reconstructions were statistically significant (p =.009). Additionally, the R2 value in most models indicated a high degree of correlation (>85%). Conclusion: The occurrence of Gram-negative enteric rods and Pseudomonas was associated with deteriorated clinical parameters in patients with peri-implant disease. © 2020 John Wiley & Sons A/S. Published by John Wiley & Sons Ltd